Problems of Studying Speech Parts in Linguistics - Tukhtasinovich, Akramov Shukurjon (European Journal of Life Safety and Stability (2660-9630), 2021)
The article is characterized by the formation of the problem of parts of speech in linguistics, in particular, in Turkish and Uzbek linguistics, as well as the existence of an effective solution to overcome the difficulties of distinguishing certain syntactic parts. In the process of syntactic communication, it is emphasized that the ability of linguistic units to expand through their valence capabilities can be a solution to some of the problems in distinguishing parts of speech.